Molecular plasmonics : theory and applications - Chegel, Volodymyr; Lopatynskyi, Andrii (Singapore : Jenny Stanford Publishing, 2020)
This book summarizes the results of studies of molecules and molecular complexes using techniques based on surface plasmon resonance (SPR) in a novel scientific direction called molecular plasmonics. It presents the current state of investigations in the field of molecular plasmonics and discusses its two main physical phenomena: surface plasmon-polariton resonance (SPPR) and localized SPR (LSPR). Among the mathematical methods for the calculation of plasmonic systems response, the book emphasizes models based on the transfer-matrix method, Green function formalism, Mie scattering theory, and numerical methods. It considers the possibilities of the SPPR technique for registering conformational changes, surface plasmon-mediated photopolymerization, electrochemical processes, as well as reversible optoelectronic and physicochemical properties during investigation of molecular systems. It describes applications of the LSPR method, including creation of metamaterials, surface-enhanced fluorescence, and bio- and chemosensing using noble metal nanoparticles in colloidal, array, and composite polymeric film formats. It also highlights the development and applications of plasmonic nanochips.
1. Molecular Plasmonics 2. Physics of the Phenomenon and Theoretical Background of Surface Plasmon Resonance Method 3. Plasmonic Nanochips Development and Applications 4. Peculiarities of Surface Plasmon Resonance Method Application for the Investigation of Biomolecules and Biomolecular Interactions 5. Application of Molecular Imprinting for Development of Plasmonic Bio- and Chemosensors 6. Electrochemical Surface Plasmon Resonance and its Applications in Biosensing, Bioelectronics, and Material Science 7. Studies of Conformational Changes in Molecular Systems using Surface Plasmon Resonance 8. Gold Nanoparticle Modification and Aggregation -- Applications from Bio- and Chemosensing to Drug Development 9. Metamaterials with Reversible Optoelectronic and Physicochemical Properties
OCLC-licensed vendor bibliographic record.
Keywords: Plasmons (Physics); TECHNOLOGY / Material Science